Learning Biology Using Real Object, ICT, and Blended Learning to Improve Factual and Conceptual Knowledge - Suyanto, S.; Suratsih, S.; Aprilisa, E.; Limiansi, K. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
During the pandemic of COVID-19, online learning was introduced, and the students' achievement decreased. This research aimed to find the effect of the biology learning model by using real objects (RO), ICT, and Blended Learning (BL) on students’ factual and conceptual knowledge. The research design was a quasi-experiment with a pretest and posttest comparison group design. This research was done in two senior high schools. Cluster random sampling was used to choose three groups of RO, ICT, and BL, involving two biology teachers and 139 students. The instrument was mainly tests of factual and conceptual knowledge. The test items were validated by expert judgment and an empirical test. Multivariate analysis was applied to test the difference in the effect of the three learning models. The results indicate that (1) RO gives the highest students’ achievement in factual knowledge, (2) ICT increases students’ conceptual knowledge, and (3) BL improves both factual and conceptual knowledge. Therefore, it is concluded that learning biology should use RO and ICT through BL to improve factual and conceptual knowledge.